2011
DOI: 10.1002/ar.21474
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsal Sagittal Venous Sinus Anatomical Variations in Brachycephalic, Dolichocephalic, and Mesocephalic Dogs and Their Significance for Brain Surgery

Abstract: Dorsal sagittal venous sinus (DSVS) is an encephalic structure located in the midline of brain dorsal surface, starting behind the frontal venous sinus and following the brain falx in its extension. Knowing DSVS morphology and cranial-cerebral relationships it is very important for surgeon when he is planning the placement of craniotomies, in order to prevent the damage of this structure. The main purpose of this study were to establish craniometric points that can be used as key points of neurosurgical import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Dorsal to the LCF is the dorsal sagittal venous sinus (DSVS). Carreira et al () reported that, in the D and in M groups, the DSVS presents dilated anterior and posterior regions and a narrow middle region, similar to the LCF morphology. However, in the B group, the DSVS assumes a triangular morphology with a posterior base (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Dorsal to the LCF is the dorsal sagittal venous sinus (DSVS). Carreira et al () reported that, in the D and in M groups, the DSVS presents dilated anterior and posterior regions and a narrow middle region, similar to the LCF morphology. However, in the B group, the DSVS assumes a triangular morphology with a posterior base (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, in the B and M groups we should consider the vault anterior area, and in the D group the vault posterior area, respectively. human medicine, there are only a few references to their location and use in veterinary medicine (Onar et al, 2001;De Machado et al, 2007;Schmidt et al, 2011;Carreira et al, 2011;Onar et al, 2012). The five craniometric points selected were quite useful to understand LCF anatomical morphology, its projection over the external skull surface, and to establish cranioencephalic relationships between the LCF and the vault.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies determined that the anatomy of the canine brain varies between breed types [47,48], as for example, in brachycephalic dogs, the rostral cranial fossa is shorter than in dolichocephalic dogs and the ethmoidal fossa is less deep, thus the position of the frontal lobe and the olfactory bulbs in brachycephalic breeds may differ from breeds with other skull types [49]. There is also a difference between the frequency of occurrence of the known shape variations among the sulci [50].…”
Section: Methodsmentioning
confidence: 99%